2017
DOI: 10.33607/bjshs.v4i107.36
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Involvement in Long- Term Regular Physical Activity and Memory: Preliminary Results

Abstract: Background. Ageing of the Western Society has become both – economic and social concern. Ageing has both – biological and psychological consequences, and, with changes in the brain due to ageing (e.g. decline in the brain volume in frontal, parietal and temporal areas, as well as hippocampus (Colcombe et al., 2003; Erickson, Voss, Shaurya, Basak, & Szabo, 2011)), there are changes in cognitive functioning. For the past years, research has indicated a relationship between aerobic activity inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…However, our results were in contrast to previous work (Tseng et al, 2013) that reported a relationship between aerobic physical activity and white matter integrity. Results from the present study partially comply with results from preliminary analysis reported by Sneidere et al (2017), in which participants with professional sports' experience were compared with active and sedentary seniors. Similarly, there were no significant relationships between long and short-term memory performance; however, significant correlation between athletic fitness and working memory performance was found.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our results were in contrast to previous work (Tseng et al, 2013) that reported a relationship between aerobic physical activity and white matter integrity. Results from the present study partially comply with results from preliminary analysis reported by Sneidere et al (2017), in which participants with professional sports' experience were compared with active and sedentary seniors. Similarly, there were no significant relationships between long and short-term memory performance; however, significant correlation between athletic fitness and working memory performance was found.…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted by Young et al (2016) found no differences between professional athletes with at least 20 years highendurance physical activity experience and age-related sedentary peers in cognitive performance, while identifying differences in white matter integrity (specifically axial diffusivity) (Young et al, 2016). In contrast, preliminary results published by Sneidere et al (2017) found higher working memory scores in participants involved in competitive sports and regularly active (e.g. Nordic Walkers, cyclists, swimmers) compared to age-matched sedentary participants.…”
Section: Introductionmentioning
confidence: 97%